Effectiveness of a mental health literacy programme in reducing stigma in young people in Póvoa de Varzim - Ana Lia Moura; Barbara Monteiro; Maria João Trigueiro; Vitor Simões Silva; Raquel Simões de Almeida; Paula Portugal; Sara Sousa; Filipa Campos; Ana Paula Soutelo; Paulo Veloso; António Marques (RevSALUS, 2025)
Introduction: Although Western society has evolved culturally in the last century, moving towards liberalisation and democratisation, many prejudiced and stigmatising behaviours are still visible, especially towards minorities. Stigma is then perceived as the marginalisation and devaluation of certain individuals based on characteristics considered as different. Objective: The main objective is to evaluate the effectiveness of the intervention programme "Bicho de 7 Cabeças", aimed at reducing mental health stigma in the young population of Póvoa de Varzim, through the promotion of mental health literacy. Methods: A quasi-experimental study was carried out, involving a sample of 504 participants attending the 9th grade in educational establishments in Póvoa de Varzim. Participants were divided into an experimental group, which received an intervention with educational sessions, and an active control group, which received an intervention with the delivery of informative content. The evaluation was carried out through a questionnaire in digital format, composed of sociodemographic questions and the instrument - Reported and Intended Behaviour Scale (RIBS). Results: There was a decrease in stigma levels in both groups (p<0.001), and the interaction value between the intervention effect and the RIBS score was equal (p<0.001). Conclusion: The effectiveness of the Mental Health Literacy promotion programme "Bicho de 7 Cabeças" in reducing the levels of stigma in young people from Póvoa de Varzim was found.